Failure to follow evidence‐based best practice guidelines in the treatment of severe acute pancreatitis. Issue 10 (13th September 2013) - Vlada, Adrian C.; Schmit, Bradley; Perry, Andrew; Trevino, Jose G.; Behrns, Kevin E.; Hughes, Steven J.
Abstract: Objectives: Evidence‐based guidelines for the treatment of severe acute pancreatitis have been established. This study was conducted to investigate the hypothesis that deviation from guidelines occurs frequently. Methods: With institutional review board approval, the outside medical records of patients with severe pancreatitis who were transferred to the study institution during the period from July 2005 to May 2012 were reviewed. Severe pancreatitis was defined using the Atlanta Classification criteria. Records were reviewed with respect to published guidelines defining the appropriate use of imaging, antibiotics and nutritional support. Results: A total of 538 patients with acute pancreatitis were identified. Of 67 patients with severe acute pancreatitis, 44 (66%) were male. The mean age of the patients was 55 years. Forty‐five of 61 (74%) patients for whom relevant data were available were imaged upon admission, but only 15 (31%) patients were imaged appropriately by computerized tomography with i.v. contrast to assess the presence of necrosis or other complications. In patients for whom relevant data were available, prophylactic antibiotics were initiated in the absence of culture data or a specific infectious target in 26 (53%) patients. Total parenteral nutrition (TPN) was administered to 38 (60%) of 63 patients for whom relevant data were available; only 10 (17%) patients received enteric feeding. No nutritional support was provided to 15 (23%) patients. Conclusions: Adherence to best practice guidelines in the treatment of severe pancreatitis is poor. The consistent application of current knowledge might improve outcomes in these patients.